Study of lncRNADSCR9 expression rate in colorectal cancer patients - Mehrnoosh Davoodi; Noosha Zia Jahromi (مجله دانشگاه علوم پزشکی بیرجند, 2023)
Background and Aims: Studies have shown that lncRNA DSCR9 prevents cancer and inflammation and its expression leads to anti-tumor activity. Therefore, this study aimed to investigate the relationship between lncRNA DSCR9 expression and the risk of colon cancer. Materials and Methods: Samples were taken from 20 tissues of patients with colorectal cancer and 20 healthy intestinal tissues of healthy individuals. Total RNA extraction was performed, followed by cDNA synthesis. Expression of lncRNA DSCR9 was investigated using real-time reverse transcription–polymerase chain reaction and primers designed using Beacon Designer software. The relative expression of lncRNA DSCR9 was calculated, and finally, the results were analyzed by GraphPad Prism software. Results: The results showed that lncRNA DSCR9 expression increased in colorectal cancer compared to the control group as well as in tumors of metastatic and non-metastatic individuals. However, the relative expression of lncRNA DSCR9 in tumors of individuals with stages 1 and 2 and in tumors of with different sizes did not show a significant increase; nevertheless, the relative expression of lncRNA DSCR9 in tumors of grades 1 and 2 was statistically significant (P=0.0144). The specificity and sensitivity of lncRNA DSCR9 showed that as a marker (P=0.0001), it could isolate the patient population from the healthy one. Conclusion: In the present study, there was a relative increase in the expression of lncRNA DSCR9 in patients with colorectal cancer compared to control, which possibly could be due to the activation of proteins involved in cancer and increased Wnt/beta-catenin signaling pathway and cause tumor cell growth and angiogenesis in cancer. Therefore, due to changes in the expression of the lncRNA DSCR9 gene in colorectal cancer, this gene may be used as a biomarker for the detection of tumors.